Tracking The Urban Fabrics of Kuching Waterfront - Xiang, Wong Jun; Wahid, Julaihi; A, Arzmi; A.S, Hasyim; Al Ansari, Naswan (RUAS, 2024)
Kuching Waterfront attracts researchers to evaluate its significance and contribution to urban design. The concept of urbanization in today’s society related to daily utilitarian living outlives the setting of a place. This paper examined the urban elements through the theory forwarded by leading scholars and examined the crucial role interplay in understanding and enhancing the character of the place. The analysis of the urban elements along Java Lane as the outset of the waterfront’s location in Kuching stretch until the Riverside Apartment that covers 1.3 kilo meters was declared open in 1993. By examining road infrastructure, public spaces, and architectural features along with ideas based on the theories of Lynch, Shirvani, Weisenburger, Hillier and Hanson, this research examines urban structures that contribute to context and their role in the urban landscape. Data was collected by means of field observations and interviews. The study was carried out by tracing the intricate fabric structure of the waterfront and shedding light on its significance and challenges. The research findings contribute to the development of understanding of the role of roads in the urban landscape and offer recommendations to promote sustainable urban development in Kuching.